Biodiversidad de la flora del flanco oriental del Cordón del Plata (Luján de Cuyo, Mendoza, Argentina) - Mendez, Eduardo (2009)
Biodiversity of the flora of the eastern slope of the Cordón del Plata (Luján de Cuyo, Mendoza, Argentina). Floristic catalogue. The floristic biodiversity of the eastern slope of the Cordón del Plata, Luján de Cuyo, Mendoza, Argentina, was studied along an altitudinal gradient, between 1200 and 4500 m a.s.l. For this we used a floristic list of 89 plant communities, distributed in 14 vegetation types, 5 vegetation belts and 3 phytogeographic units. For each of the species, its distribution in the groups of plant communities, phytogeographic position, life form, biogeographical origin, and registration of each collection was considered. The studied flora has 667 species, corresponding to 338 genera and 82 families. There are 8 Pteridophyta, 1 Gymnospermae, and 73 Angiospermae, of which 12 are Monocotyledons and 61 Dicotyledons. The most represented families are Asteraceae and Poaceae, which in total have 110 genera and 249 species. The most species-rich genera correspond to Senecio, Baccharis and Adesmia. Approximately 20 % of the species are endemic de Argentina. This flora it is compared with the flora of the country, the province and other areas.